Habilitation and rehabilitation of patients with traumatic brachial plexopathy involving the use of the EXAR 34 passive exoskeleton - Olga V. Kurushina; Alexander A. Vorobyov; Fedor A. Andryushchenko; Dmitry I. Nezhinsky (LLC "MEDIAFORMAT", 2024)
Recovery after traumatic plexitis is a complex and lengthy process that requires rehabilitation measures involving the use of both conventional methods, such as drug therapy, therapeutic exercise, physical therapy, and psychological counseling, and innovative technologies, such as EXAR 34 passive upper limb exoskeleton.